Multidrug-Resistant Bacterial Infections in Geriatric Hospitalized Patients before and after the COVID-19 Outbreak: Results from a Retrospective Observational Study in Two Geriatric Wards - Gasperini, Beatrice; Cherubini, Antonio; Lucarelli, Moira; Espinosa, Emma; Prospero, Emilia (Antibiotics (Basel), 2021)
The impact of the COVID-19 pandemic on multidrug-resistant (MDR) bacteria is unknown. The purpose of this study was to assess prevalence, etiology, and association with mortality of MDR bacteria in older adult patients before and after the first peak of the COVID-19 pandemic in Italy. An observational retrospective study was conducted in two geriatric wards of the Azienda Ospedaliera Ospedali Riuniti Marche Nord, Fano, and of the INRCA, IRCCS, Ancona, in the Marche Region, Italy, from December 2019 to February 2020 and from May to July 2020. A total of 73 patients (mean age 87.4 ± 5.9, 27.4% men) and 83 cultures (36 pre-COVID-19 and 47 post-COVID-19) were considered. Overall, 46 cultures (55.4%) reported MDR bacteria (50% in pre- and 59.6% in post-COVID-19 period, p = 0.384). MDR bacteria in bloodstream significantly increased in post-COVID-19 period (68.8% vs. 40.0% p = 0.038) and MDR bacteria in urine did not change (51.6 vs. 54.8%, p = 0.799). Escherichia coli was the main MDR bacterium in pre-COVID-19, p = 0.082 and post-COVID-19, p = 0.026. Among patients with MDR infection, in-hospital mortality was 37.5% and 68.8% in pre- and post-COVID-19, respectively (p = 0.104), and mortality at 30 days was higher in post-COVID-19 period (78.9% vs. 27.3%, p = 0.012). An increased number of MDR bacteria in bloodstream and mortality after MDR infection have been observed in the post-COVID-19 period.